Mechanism of TRPM2 channel gating revealed by cryo‐EM. (10th June 2019) - Xia, Shiyu; Wang, Longfei; Fu, Tian‐Min; Wu, Hao
Abstract : Transient receptor potential melastatin 2 (TRPM2) is a non‐selective cation channel that allows Ca 2+ influx across the plasma membrane and efflux from lysosomes upon opening. TRPM2 is best known as a biosensor of reactive oxygen species (ROS), which mediates some of the body's responses to oxidative stress. As such, TRPM2 is involved in a plethora of biological processes including immune response, insulin secretion, body temperature control and neuronal cell death, and represents an emerging therapeutic target for many human diseases, from diabetes to inflammatory and neurodegenerative diseases. A direct ligand of TRPM2 is ADP‐ribose (ADPR), which accumulates in cells at high levels of ROS, and activates TRPM2 synergistically with intracellular calcium (Ca 2+ ). Here, we describe recent cryo‐electron microscopy (cryo‐EM) structures of TRPM2 and summarize the insights they provided into the gating mechanism of the channel. Abstract : Transient receptor potential melastatin 2 (TRPM2) is a non‐selective cation channel gated by ADP‐ribose (ADPR) and calcium (Ca2+). A recent structural study revealed the gating mechanism of human TRPM2, with priming by ADPR as the first step followed by Ca2+‐induced channel opening. The human TRPM2 structures, together with the structures of its zebrafish and sea anemone homologs, provided an in‐depth mechanistic picture of TRPM2 channel gating across species.